The reality of the availability of teaching techniques from the faculty members’ point of view at the Faculty of Science and Arts in Al-Ula Branch of Taibah University - Jarrah, Yousef Mufleh Saleem (Journal of Educational and Psychological Sciences, 2020)
The current study aimed to know the reality of the availability of teaching techniques from the faculty members’ point of view at the Faculty of Science and Arts in Al-Ula at Taibah University, and the effects of non-availability for these techniques. The researcher used the descriptive approach, and the study sample consisted of all members of the original community who are (121) faculty members (male, female). The researcher prepared a questionnaire consisting of (42) techniques for gathering information, and it was verified validity and reliability. The study has come across the following results: It was found that the average mean of the reality of the availability of teaching techniques was satisfactorily with an average of (2.41), and (50.1%) percentage with a degree (disagree) and that is the highest degree of availability of five techniques with a general average of (4.30) and with a (54.4%) percentage with a degree (agree). As for the general mean for the medium techniques, it was (1.84) with a (46.1%) percentage and with a degree (disagree). The lowest levels of those technologies, which are almost non-existent, were with a general average (1.45) with a (68.6%) percentage and a degree (strongly disagree). As the results indicated there are statistically significant differences in the opinions of the study sample individuals on the reality of the availability of teaching techniques according to the gender variable at the level of the tool as a whole in favor of males. Finally, in the light of the results of the study, also the negative effects of the lack of teaching techniques in Science and Arts in Al-Ula were clearly seen and the feasibility of the study as well. The study also concluded to feasibility of the study the reality of the techniques in the college and strengthening the practical side in using the modern methods of the teaching and diversity in exchange of information with the learner, and developing the self abilities for the learner. This study is concluded with several recommendations, the most important of which are: the university administration should ensure the availability of teaching techniques in colleges, keep pace with technological developments, and conduct more future research on ensuring digital quality and the possibility of integration in curriculum design.
Keywords: Teaching techniques; Learning environments; University teaching